Color me khmao: the effects of social factors on colorism among Khmer women - Vanessa Lakana Veak (Frontiers in Sociology, 2025)
IntroductionGiven the lack of academic literature on colorism within the Cambodian community and the lack of focus on how colorism influences experiences in this context, this study seeks to analyze how Khmer women’s perceptions of colorism are shaped by their family and community environments.MethodsThe data and methods consist of 40 in-depth qualitative interviews with Khmer women, primarily those living in the United States and Cambodia, with their experiences of colorism analyzed through thematic analysis.ResultsFindings reveal that factors such as family support and cultural connections to Khmer identity interact with relative skin tone within families and broader communities to shape self-esteem and experiences with colorism. Women with darker skin did not necessarily have the lowest self-esteem, especially when they had supportive families and lived in communities where darker skin tones were more prevalent. Conversely, women with lighter skin did not necessarily have the highest self-esteem, especially when their families reinforced color hierarchies and they lived in communities dominated by White or East Asian Americans.DiscussionBy further examining this structural issue, colorism, the study highlights how communities of color can work toward racial and ethnic justice while developing strategies for future generations to challenge and move beyond colorism.